Prospects in non-invasive diagnosis of bronchial asthma-related gastroesophageal reﬂux disease: a single-stage open uncontrolled non-randomised observational study - E. V. Gorban; E. S. Kameneva; V. V. Gorban (Кубанский научный медицинский вестник, 2021)
Background. Respiratory symptoms of bronchial asthma (BA) comorbid with gastroesophageal reflux disease (GERD) may provoke duodenogastroesophageal reflux (DGER) via aggressive agents like pepsinogens and bilirubin.Objectives. A clinical and functional study of the saliva pepsinogen and bilirubin-associated BA-comorbid GERD for non-invasive DGER diagnosis.Methods. A total of 29 patients with an allergic BA phenotype, comorbid GERD and 50,2 ± 2,4 years mean age have been examined. Biochemical blood panel included bilirubin, C-reactive protein and allergen-specific IgE. Saliva bilirubin was estimated in colorimetry, and the pepsinogen-1, -2 content — in immunological tests. Grade A–D reflux oesophagitis (RO) in oesophagoscopy was assigned to erosive reflux disease, and grade N–M oesophageal mucosa (OM) lesions — to non-erosive reflux disease. External respiratory function (ERF) was assessed with forced expiratory volume (FEV1, L/s), forced vital capacity (FVC), Tiffeneau index (FEV1/FVC), pre- and post-berodual FEF1 and FVC dynamics.Results. The BA–GERD patients were markedly polymorbid. Cough and chest tightness associated with age, and the tight chest rate — with a higher body mass index and lower FEV1/FVC. The association between higher pepsinogen-I and lower FEV1/FVC–FVC in response to inhaled berodual, as well as between higher saliva bilirubin and lower FVC–FEV1 after berodual intake reflects a significant high-DGER effect on BA representation.Conclusion. In BA–GERD patients, saliva pepsinogen and bilirubin are biomarkers of both DGER and respiratory inflammation with bronchospasm.